Implementation Of Minimum Service Standards (Mss) In The Pharmaceutical Field At Pharmaceutical Installations At Royal Prima Hospital - Firdha Amelia; Karmila Kaban; Sri Wahyuni Nasution; Adrian Khu (International Journal of Health and Pharmaceutical (IJHP), 2022)
Minimum Service Standards (MSS) are provisions regarding the type and quality of basic services which are mandatory regional affairs that every citizen has the right to obtain at a minimum. Withthe preparation of MSS, it is hoped that it can help implement the implementation of Minimum Service standards in hospitals. Knowing the implementation of minimum service standards (MSS) for the pharmaceutical hospital in the pharmacy installation of Royal Prima Hospital. The type and design of this research are qualitative. The population in this study was 5 informants. The results showed that the minimum service standards consisting of medication errors, writing drugs according to the formulary, patient satisfaction, and waiting time for drugs had been carried out at Royal Prima Hospital. Based on the results of research on the implementation of minimum service standards (MSS) for the pharmacy sector at the pharmacy installation of Royal Prima Hospital, it can be concluded that the minimum service standards consist of medication errors, drug writing according to the formulary, patient satisfaction and waiting time for drugs have been carried out. at the Royal Prima Hospital.